IMPLEMENTASI PERATURAN DAERAH KABUPATEN AGAM NOMOR 5 TAHUN 2014 TENTANG PENGELOLAAN KELESTARIAN KAWASAN DANAU MANINJAU - Lara Miranda; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
In an effort to conserve the Lake Maninjau area the Regional Government stipulates the Regional Regulation of Agam Regency Number 5 in 2014 concerning the management of preservation of the Lake Maninjau Area. Agam Regency Government conducts 6 stages and has 10 priority agendas to preserve the Lake Maninjau area and many regional device organization involved in the implementation, but in the implementation abstacles and problems area still found. The aim of this study was to find out how the implementers and the factors that inhibited the implementation of Agam Regency Regulation Number 5 in 2014 concerning the management of preservation of the Lake Maninjau area. The theoretical concept used is Public Policy Implementation according to Grindle. This study uses qualitative research with a phenomenological approach. In data collection, researchers used interviewing, observation,and documentation techniques. By using a purposive sampling technique as a source of information and data analysis. The results of this study indicate that the process of implementing Agam Regency Regulation Number 5 in 2014 concerning the management of preservation of the Lake Maninjau area has not run well as evidenced by still many Floating Net Cages (FNC) found on Lake Maninjau. it requires a lot of funds for the preservation of the Lake Maninjau area, and the absence of Lake Maninjau zoning issued by the provincial government, and the growth of floating net cages at Lake Maninjau funded by investor. Whereas in Regional Regulation of Agam Regency Number 5 in 2014 concerning the management of preservation of the Lake Maninjau area, Article 7 stipulates how many Floating Net Cages (FNC) can be used on Lake Maninjau.Keyword: Policy, Implementation, Sustainability of Lake Maninjau Area